2019
DOI: 10.1080/02713683.2019.1666997
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism Study of Electroacupuncture for Dry Eye Syndrome by Targeting Conjunctival Cytokine Expressions

Abstract: Table 1. Baselines in the two groups M (Q25, Q75) Baselines AG EAG P value Age (year) 35 (28,53) 34 (26,48) 0.537

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…It makes up for the shortcomings of acupuncture with insufficient stimulation intensity and shows better efficacy in clinical studies. Studies have shown that, compared with acupuncture, electroacupuncture has better effects in alleviating local pain ( Aranha et al, 2015 ), regulating lipid metabolism in patients with non-alcoholic fatty liver disease, reducing inflammatory reaction ( Yu et al, 2018 ), promoting lacrimal gland secretion and stabilizing tear film ( Zhang et al, 2020a ). However, the research on the internal mechanism of electroacupuncture is not comprehensive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It makes up for the shortcomings of acupuncture with insufficient stimulation intensity and shows better efficacy in clinical studies. Studies have shown that, compared with acupuncture, electroacupuncture has better effects in alleviating local pain ( Aranha et al, 2015 ), regulating lipid metabolism in patients with non-alcoholic fatty liver disease, reducing inflammatory reaction ( Yu et al, 2018 ), promoting lacrimal gland secretion and stabilizing tear film ( Zhang et al, 2020a ). However, the research on the internal mechanism of electroacupuncture is not comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive system: electroacupuncture inhibits NF-κB/NLRP3 pathway ( Zhang et al, 2017 ). Immune system: electroacupuncture inhibits NLRP3 inflammasome by down-regulating the expression of Cathepsin-B ( Zhang et al, 2020a ). Others: electroacupuncture inhibits ROS/TXNIP/NLRP3 pathway; electroacupuncture inhibits NLRP3 inflammasome by up-regulating CB2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15 , 16 ] Acupuncture can affect the tissue morphology of functional units, restore damaged corneal tissue, improve dry corneal morphology, and promote the rehabilitation of ocular surface structures, [ 17 ] activate the synthesis function of lacrimal gland, restore secretion function, and improve the inherent morphology of the lacrimal gland [ 18 ] ; Acupuncture can affect the nerve regulation of tear secretion, effectively stimulate the activity of parasympathetic nerves, [ 19 ] promote the release of acetylcholine from nerve endings, and increase the content of acetylcholine in the lacrimal glands, thereby increasing the secretion of tears [ 20 ] ; It can reduce the inflammation of the ocular surface, effectively reduce the concentration of tumor necrosis factor and interleukin 4 in the tears of patients, and improve the signs of patients with Dry Eye [ 21 ] ; Acupuncture can inhibit cytotoxicity and alleviate cell apoptosis in lacrimal glands and ocular surface epithelial tissues in patients with dry eye [ 22 , 23 ] ; acupuncture can adjust the level of hormones and regulate the related functions of ocular surface hormone receptors. [ 24 ] Acupuncture can regulate the blood circulation around the eyes, promote self-repair of eye tissues, improve ocular symptoms, [ 25 ] adjust the quality and quantity of tears, and improve the ocular microenvironment. [ 26 ] It is worth noting that during the treatment of Dry Eye by acupuncture, operators shall pay attention to the depth and technique of acupuncture when needling on the points, such as Jingming and Chengqi.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Furthermore, Zhang et al have concluded that electroacupuncture can effectively regulate the conjunctival cytokine expressions. [ 26 ] However, lacking of large samples of multi-center RCTs and strong evidences in the management of DED somewhat restrict the wide application of acupuncture clinically.…”
Section: Introductionmentioning
confidence: 99%